Experimental investigation of mid-infrared laser action from DY3+ doped fluorozirconate fiber - Sójka, Lukasz; Pajewski, Lukasz; Popenda, Maciej; Beres-Pawlik, Elzbieta; Lamrini, Samir; Markowski, Konrad; Osuch, Tomasz; Benson, Trevor M.; Seddon, Angela B.; Sujecki, Slawomir (Institute of Electrical and Electronics Engineers, 2018)
Efficient continuous-wave laser operation at 2.982 μm is achieved with a Dy3:fluoride fiber pumped using an inhouse-built 1.1 μm ytterbium (III) fiber laser. The laser output power reached is 554 mW, with a maximum slope efficiency of 18% with respect to the launched pump power. Additionally, the measured spontaneous luminescence within the visible wavelength range, under 1.1 μm pumping, is presented and attributed to excited state absorption (ESA). The influence of the ESA on the laser performance is discussed. The results confirm that high output powers from Dy: fluoride fiber laser pumped at 1.1 μm are possible.